New syllabus primary mathematics workbook 4B - Yee, Dr. Foong Pui (Karachi: Oxford University Press., 2024)
New Syllabus Primary Mathematics Workbook 4B is a supplementary resource that builds on the concepts introduced in the Primary Mathematics 4 textbook. It covers topics such as decimals, measurement, geometry, and data analysis, offering a variety of exercises aimed at enhancing students' problem-solving abilities and critical thinking. The workbook is designed to reinforce key mathematical principles through step-by-step practice and real-world applications. With a focus on independent learning, this workbook helps students solidify their understanding and prepares them for more complex mathematical challenges in the future.